2015
DOI: 10.1093/jxb/erv299
|View full text |Cite
|
Sign up to set email alerts
|

A geminivirus betasatellite damages the structural and functional integrity of chloroplasts leading to symptom formation and inhibition of photosynthesis

Abstract: HighlightA satellite DNA-encoded protein (βC1) is localized in the chloroplast. The intercellular events associated with βC1-induced photosynthetic inhibition and vein clearing symptom formation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 50 publications
7
82
0
Order By: Relevance
“…2), manifesting the detrimental effect of βC1 in plant photosynthesis. Thus, our data are consistent with the previous findings in which βC1 was associated with reduced Chl amounts and development of yellowing symptoms (Bhattacharyya et al, 2015; Funayama-Noguchi and Terashima, 2006; Rong et al, 2018). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…2), manifesting the detrimental effect of βC1 in plant photosynthesis. Thus, our data are consistent with the previous findings in which βC1 was associated with reduced Chl amounts and development of yellowing symptoms (Bhattacharyya et al, 2015; Funayama-Noguchi and Terashima, 2006; Rong et al, 2018). …”
Section: Discussionsupporting
confidence: 93%
“…The geminiviruses betasatellite-encoded βC1 gene acts as a symptom determinant, suppresses transcriptional or posttranscriptional gene silencing and affects jasmonic acid responsive genes (Zhou, 2013). βC1 of RaLCB has been reported to reduce the amount of Chl and alter the quantity of PSII-related proteins in N. benthamiana (Bhattacharyya et al, 2015). In this study, we determined the effect of TYLCCNV and its betasatelliteencoded pathogenicity factor, βC1, on the compromised photosynthetic capability in N. benthamiana .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains unknown how the interaction of viral proteins with particular target proteins could lead the CPRGs transcriptome to global down-regulation. A recent study has shown that bC1 protein encoded by Geminivirus beta-satellite DNA has a role in vein chlorosis symptoms and inhibition of photosynthesis, which accompany the impaired chloroplasts structure and function and the reduced levels of CPRGs expression, in Nicotiana benthamiana plants [4]. It remains unclear how bC1 protein fulfills the pathogenic function.…”
Section: Introductionmentioning
confidence: 99%